PATTERNS AND FUNCTIONAL ROLES OF CODE-SWITCHING IN SHAPING STUDENTS’ LEARNING IN EFL CLASSROOM IN PUBLIC UNIVERSITIES - Ghulam Mustafa Mallah; Dr. Faraz Ali Bughio (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the pattern and functional roles of code-switching, the practice of switching from one language to another, used by students and teachers in the English as a foreign language (EFL) classroom in public sector universities in Sindh province. To address the research questions, this study employed a quantitative research approach. Data were collected from the students studying in 5 public sector universities. The quantitative data were analyzed using SPSS software, employing reliability and validity tests, correlational analysis, Cronbach’s Alpha test, t-test and frequency analysis. The result of this study reveals that code-switching was found inevitable in the EFL classrooms. Different patterns of code-switching were used by teachers and students. Teachers used code-switching to facilitate students with understanding difficult topics, for teaching grammar, for teaching technical vocabulary, and for clear instructions. Students were found more comfortable communicating with teachers and fellow students using code-switching. They increased their classroom performance through code-switching. Moreover, code-switching was found pedagogical strategy to teach the English language to multilingual students.